Antibiotic activity of pyrenomycetes under submerged conditions - Bandre, T R; Sasek, V (Folia microbiologica, 1977)
Twenty-three pyrenomycete species were tested for antibiotic activity in submerged cultures. When they were screened against bacteria and fungi, 15 showed positive results. Among these, Eutypa acharii, Diaporthe pustulata, Melanconis flavovirens and Camarops microspora were quite promising against bacteria and/or fungi. An antibacterial antibiotic from Camarops microspora was partially purified and characterized.
Keywords: Microbial Sensitivity Tests; Ascomycota; ponoření; mikrobiální testy citlivosti; Bacteriological Techniques; Anti-Bacterial Agents; Immersion; Bacillus subtilis; antibakteriální látky; bakteriologické techniky; Candida